2021
DOI: 10.21203/rs.3.rs-600797/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PET Microplastics Affect Human Gut Microbiota Communities During Simulated Gastrointestinal Digestion. First Evidence of Plausible Polymer Biodegradation During Human Digestion

Abstract: Microplastics are a widely recognized global problem due to their prevalence in natural environments and the food chain. However, the impacts of microplastics on human microbiota and their possible biotransformations during the gastrointestinal tract have not been well reported. To evaluate the potential risks of microplastics at the digestive level, completely passing a single dose of polyethylene terephthalate (PET) through the gastrointestinal tract was simulated by combining a harmonised static model and t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…SIMGI can also be used to study the dysbiotic microbiota associated with an inadequate diet or any pathological condition, such as obesity or inflammatory bowel disease, where the dysbiotic microbiota obtained from a patient is stabilized in the system (Barroso et al, 2015a; Dupont et al, 2019). Furthermore, being one of the latest systems, SIMGI is still evolving and is used successfully to study, for example, dietary substances rich in polyphenols (Cueva et al, 2015; Gil‐Sánchez et al, 2020; Tamargo, Cueva, et al, 2022), the prebiotic potential of citrus pectin (Ferreira‐Lazarte et al, 2019), prebiotic induced reduction in lipid bioaccessibility (Tamargo et al, 2020), and effect of microplastic on human gut microbiota (Tamargo, Molinero, et al, 2022).…”
Section: Dynamic Modelmentioning
confidence: 99%
“…SIMGI can also be used to study the dysbiotic microbiota associated with an inadequate diet or any pathological condition, such as obesity or inflammatory bowel disease, where the dysbiotic microbiota obtained from a patient is stabilized in the system (Barroso et al, 2015a; Dupont et al, 2019). Furthermore, being one of the latest systems, SIMGI is still evolving and is used successfully to study, for example, dietary substances rich in polyphenols (Cueva et al, 2015; Gil‐Sánchez et al, 2020; Tamargo, Cueva, et al, 2022), the prebiotic potential of citrus pectin (Ferreira‐Lazarte et al, 2019), prebiotic induced reduction in lipid bioaccessibility (Tamargo et al, 2020), and effect of microplastic on human gut microbiota (Tamargo, Molinero, et al, 2022).…”
Section: Dynamic Modelmentioning
confidence: 99%
“…Furthermore, both PE and tetrabromobisphenol A, a plastic additive, transformed the composition of the microbiota and the metabolism pathways, altering gut homeostasis (Huang, Yin, et al, 2021). Regarding dynamic multi‐compartmental models, of the few studies available (Godoy et al, 2020; Tamargo et al, 2022; Yan, Zhang, et al, 2022), Tamargo et al (2022) were among the first to evaluate the effects of MPs on human fecal bacteria. Simulating the entire gastrointestinal tract (stomach, small intestine, and three parts of the colon) by combining a harmonized static model and the dynamic gastrointestinal simgi® model, they showed that PET MPs (166 mg/intake, 160 ± 110 μm, irregular shape) reduced biodiversity and altered the composition of the colonic microbiota, possibly due to the attachment of some colonic microbiota to MP surfaces.…”
Section: Focus On Human Health Implications: the Need To Investigate ...mentioning
confidence: 99%
“…Simulating the entire gastrointestinal tract (stomach, small intestine, and three parts of the colon) by combining a harmonized static model and the dynamic gastrointestinal simgi® model, they showed that PET MPs (166 mg/intake, 160 ± 110 μm, irregular shape) reduced biodiversity and altered the composition of the colonic microbiota, possibly due to the attachment of some colonic microbiota to MP surfaces. Different types of bacteria were affected, in particular a decrease in beneficial bacteria as Christensenellaceae was observed, as well as an increase in the proportions of Escherichia/Shigella and Bilophila , often associated with a pro‐inflammatory effect in the gut (Tamargo et al, 2022). More important, the same authors described a bidirectional interaction between MPs and the microbiota for the first time.…”
Section: Focus On Human Health Implications: the Need To Investigate ...mentioning
confidence: 99%
See 2 more Smart Citations